A Literature Review: Teori Sinyal dan Keputusan Investasi - Putri Sion (JASS (Journal of Accounting for Sustainable Society), 2024)
Previous research is a crucial aspect of a scientific article. It serves to strengthen theories and the relationships between variables. This article aims to analyze how signal theory influences investors' decision-making in investment activities. Investment is an activity in which an investor allocates funds in the present with the expectation of gaining returns in the future. Signal theory, developed by Ross in 1977, emerged from the issue of asymmetric information between a company's management and stakeholders who require that information, such as investors. The method employed in this study is qualitative analysis, relying on journals, case studies, and books that are relevant, highly relevant, or sufficiently relevant. The findings of this literature review indicate that signals—information provided by a company to parties requiring it (investors)—can significantly influence investment decisions. This research is expected to serve as a reference and consideration for investors in making informed decisions and engaging in investment activities.